Entrepreneurship performance in the European Union: In what extent do socioeconomic, environmental, and governmental conditions matter? - Luz, A. R.; Bento, P.; Paschoalotto, M.; Pereira, R. (SemeAD2021: XXIV Seminários em Administração, 2021)
The entrepreneurial ecosystem is geographically shaped by complex interconnections which enhance economic growth (Hechavarría and Ingram, 2019). Therefore, policymakers seeking to increase development levels should enforce strategies that encourage entrepreneurship (Acs et al., 2016). Extant literature distinguishes two drivers of entrepreneurship: opportunity (OPP) and necessity (NEC). The first relates to individuals who voluntarily start a business to exploit market advantages, and the second is usually a reaction to scarce employment options (Amoros et al., 2019).